Hibernoma with inflammatory features: A description of a new variant - Lukas Streich; Ximing Yang (Elsevier, 2020)
Hibernoma is an uncommon benign tumor arising from brown fat. These tumors are well-described in the literature, and occur throughout the body with the majority of cases arising in the thigh, shoulder, and upper back, with some in the retroperitoneum. Several morphologic variants have been described, including typical, spindle, lipoma-like, and myxoid. The overlap with a well-differentiated liposarcoma/atypical lipomatous tumor is well-known, and the two lesions can be differentiated by immunostaining and in-situ hybridization for MDM2. In this report, we describe a case of hibernoma with a dense lymphoplasmacytic infiltrate arising in the retroperitoneum, a morphologic variant not previously described in the literature.